Acyclovir Suppression to Prevent Clinical Recurrences at Delivery After First Episode Genital Herpes in Pregnancy: An Open-Label Trial. Issue 2 (2001) - Scott, L. Laurie; Hollier, Lisa M.; McIntire, Donald; Sanchez, Pablo J.; Jackson, Gregory L.; Wendel, George D.
Abstract : Objective: To continue evaluation of the use of acyclovir suppression in late pregnancy after first episode genital herpes simplex virus (HSV) infection, using an open-label study design. Methods: Ninety-six women diagnosed with genital herpes for the first time in the index pregnancy were prescribed suppressive acyclovir 400 mg orally three times daily from 36 weeks until delivery in an open-label fashion. Herpes cultures were obtained when patients presented for delivery. Vaginal delivery was permitted if no clinical recurrence was present; otherwise a Cesarean delivery was performed. NeonatalHSV cultures were obtained and infants were followed clinically. Rates of clinical and asymptomatic genital herpes recurrences and Cesarean delivery for genital herpes were measured, and 95% confidence intervals were calculated. Results: In 82 patients (85%) compliant with therapy, only 1% had clinical HSV recurrences at delivery. In an intent to treat analysis of the entire cohort, 4% had clinical recurrences (compared with 18–37% in historical controls). Asymptomatic shedding occurred in 1% of women without lesions at delivery. Two of the four clinical recurrences were HSV-culture positive. No significant maternal or fetal side-effects were observed. Conclusions: In clinical practice the majority of patients are compliant with acyclovir suppression at term. The therapy appears to be effective at reducing clinical recurrences after a first episode of genital herpes complicating a pregnancy.